EXPLORING MULTILINGUISTIC TEXTBOOKS AND ACTIVITIES TO ENHANCE THE COMPETENCIES OF SCHOOL STUDENTS TO LEARN SKILLS IN ENGLISH IN A BETTER WAY. - G., Mary Sunanda (ShodhKosh: Journal of Visual and Performing Arts, 2024)
"School is the miniature of society",said John Dewey ( The School and Society (1899). Indian community is a multilingual community. We can come across multi lingual community in Hyderabad also. In ICSE, CBSE, schools of Hyderabad and Secunderabad. We come across students from different mother tongues, say, Bengali, Marathi, Kannada, Tamil, Malayalam, Gujrath, Hindi etc. In the last three decades Hyderabad city has witnessed growth of CBSE, ICSE schools, apart from functioning of KV’s and JNV’s.Around the same time Govt in AP and T.S had both Telugu medium and English medium schools .The instruction was in Telugu in English medium schools, the English reader prescribed was different for Telugu and English medium students. In these schools, children mostly come from not so wealthy family. Since 2014, the same English text book has been prescribed for Telugu and English schools. It was decided that Telugu medium students also have to study English from class1. Language learning to any child comes from birth – if one child is exposed to different languages in childhood, then the academic outcome of that child’s behavior, attitude, skills etc would be different. One aspect of multilingualism that has not been systematically examined is the typology of multilinguals' languages: Do variations in languages multilinguals are exposed to contribute to the development of their cognition and brain? Olga Kepinska, et al, investigated n = 162 5–6-year-olds with different language backgrounds on a monolingual-to-quintilingual continuum. The results show that typological linguistic diversity can be related to expressive vocabulary knowledge in the dominant language. To study the topic, “ Exploring Multilinguistic textbooks and activities to enhance the competencies of school students to learn skills in English ‘. I selected the text book series “Our World through English ” T.S 1-X class.